2(-3x+1)=4(x-2)

Simple and best practice solution for 2(-3x+1)=4(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-3x+1)=4(x-2) equation:


Simplifying
2(-3x + 1) = 4(x + -2)

Reorder the terms:
2(1 + -3x) = 4(x + -2)
(1 * 2 + -3x * 2) = 4(x + -2)
(2 + -6x) = 4(x + -2)

Reorder the terms:
2 + -6x = 4(-2 + x)
2 + -6x = (-2 * 4 + x * 4)
2 + -6x = (-8 + 4x)

Solving
2 + -6x = -8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
2 + -6x + -4x = -8 + 4x + -4x

Combine like terms: -6x + -4x = -10x
2 + -10x = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
2 + -10x = -8 + 0
2 + -10x = -8

Add '-2' to each side of the equation.
2 + -2 + -10x = -8 + -2

Combine like terms: 2 + -2 = 0
0 + -10x = -8 + -2
-10x = -8 + -2

Combine like terms: -8 + -2 = -10
-10x = -10

Divide each side by '-10'.
x = 1

Simplifying
x = 1

See similar equations:

| 4(j+-1)=-16 | | (10x+2y)(4x-11y)= | | -2(5x+12)-5=6(3X-2)-10 | | t/9=-28 | | 13x+1=-13+27 | | (63x+50y)-(19x-17y)= | | (2-z)(4z+5)=0 | | -10+(-2)=-6x | | 2(w-13)=12 | | 3(j-20)=-3 | | 15x-17=3+10x | | 1-3n=16-6n | | 15x^2y+8xy^2+y^3=0 | | (6p+7q)(-2p+10q)= | | 8n^2-18N-5=0 | | 3(C-D)D= | | p^2-15p+50=0 | | (4u+9)(1-u)=0 | | 7/8a-5/3a | | 8n-(5n+4)=17 | | x^1/2=13 | | (4u+9)(1-0)=0 | | 5y-3y+7=4y+7-2y | | 6y+2y=26 | | -3(4b-10)=12(24+60) | | sqrt(x)=13 | | 3(x+2)+2(x+4)=-1 | | 2(3+2x)+3(x-4)=8 | | 9(7x-3)=1+2x | | 2x^2+17x+10=0 | | -12=-12a | | 25x+15=24x+10 |

Equations solver categories